ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS BERDASARKAN GAYA BELAJAR PADA MATERI POLA BILANGAN - Yashinta Nurul Khoirunnisa, - (2021)
Mathematical communication helps in wheter or not students to inform the mathematical ideas orally or in writing, to inform the ideas students will be different because when the students absorb, organize, and process the information obtained different. The material of Number patterns used of this research, because they relate to many problems of everyday life. This research aims to analyze mathematical communication ability in terms of learning styles on number patterns material. Research method used descriptive qualitative and the research subject were students on 8-th grade the one of junior high school in Bandung. Data collected by learning styles questionnaires, mathematical communication ability writing test, and interview to students. The research result showed that there were 10 students of visual learning styles, 12 students of auditory styles, 6 students of kinesthetic styles. Mathematical communication ability in each learning styles tend to be moderate. Conclusing the pictures and difficulty understanding and interpreting the question become students' difficulties on mathematical communication in each learning styles. Factors affecting of mathematical communication on the visual learning style are uncomfortable conditions and communication with teacher, the auditory learning style are the explanation of the material that is less clear and difficult to understand learning, the kinesthetic learning style are not focused and afraid will not accepted or heard when they inform the opinions.